Enhancing Workplace Harmony in Malaysia: Integrating Japanese Kaizen and Ringi Management Practices into Industrial Relations - Ismail, Fadillah; Tai Wei Hong (JBS Nexus, 2025)
This study examines the adoption of Japanese Kaizen and Ringi management practices to address workplace challenges in Malaysia. Kaizen fosters continuous improvement by involving employees at all organizational levels, leading to enhanced productivity and job satisfaction. Ringi emphasizes consensus-based decision-making, promoting inclusivity and addressing communication barriers in Malaysia’s traditionally hierarchical management structures. These practices align with recent industrial relations reforms, such as the Industrial Relations Amendment Act 2020, to create a more cooperative and engaging work environment. The findings underscore that adapting these methods to Malaysia’s cultural and legal contexts can drive significant improvements in workplace harmony, reduce turnover, and foster sustainable organizational growth. Gradual implementation, pilot programs in key sectors, and tailored training modules are recommended to ensure effective integration. This study highlights the potential of Kaizen and Ringi to revolutionize Malaysian industrial relations by aligning employee motivation with organizational goals for long-term success.